IN WHICH REGIONS ARE LEGENDS MORE COMMON? (Universal International Scientific Journal, 2026)
This article analyzes the regional distribution of legends and examines the areas where they are most common. Using England and Uzbekistan as case studies, the research explores how historical events, religious centers, sacred sites, and natural landscapes influence the formation and preservation of legends. The study highlights the connection between legends and cultural memory, national identity, and oral storytelling traditions. Regions such as Sherwood Forest, Cornwall, Yorkshire, as well as Bukhara, Samarkand, and Khorezm are examined as examples of legend-rich areas.
Keywords: legend, folklore, regional distribution, cultural memory, oral tradition, cultural heritage, Sherwood Forest, Bukhara, Samarkand, Khorezm, religious centers.